Perilaku Agresi pada Mahasiswa Ditinjau dari Kematangan Emosi - Aprius Maduwita Guswani; Fajar Kawuryan (Universitas Muria Kudus, 2011)
This study aimed to examine the correlation between emotional maturity with agressive behavior in collegian. Subject in this study aretechnique and law collegian in Muria Kudus University. The participants took by accidental sampling. Agressive behavior and emotional maturity scale are used to get the data. The data analysed by product moment. Coeficient correlation result the both variables is rxy=-0,906 with p=0,000 (p smaller than 0,01). Its mean there is significant negative correlation between emotional maturity and agressive behavior. More higher emotional maturity, lower agressive behavior can get, the opposite, lower emotional maturity make agressive behavior more higher. Effective giveness emotional maturity to agressive behavior is 82%.